Highly-oriented molecular arrangements and enhanced magnetic interactions in thin films of CoTTDPz using PTCDA templates. Issue 26 (17th May 2016) - Eguchi, Keitaro; Nanjo, Chihiro; Awaga, Kunio; Tseng, Hsiang-Han; Robaschik, Peter; Heutz, Sandrine
Abstract : We found the templating effect of thin layers of perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA) on the growth of cobalt tetrakis(thiadiazole)porphyrazine (CoTTDPz) thin films, which induced a significantly-enhanced antiferromagnetic interaction. Abstract : In the present work, the templating effect of thin layers of perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA) on the growth of cobalt tetrakis(thiadiazole)porphyrazine (CoTTDPz) thin films was examined. X-ray diffraction and optical absorption spectra indicate that while CoTTDPz forms amorphous thin films on the bare substrates, it forms crystalline thin films on the PTCDA templates, in which the molecular planes of CoTTDPz are considered to be parallel to the substrates. Magnetic measurements reveal a significantly enhanced antiferromagnetic interaction of CoTTDPz in the templated thin films, with values reaching over 13 K. The ability to generate crystalline films and to control their orientation using molecular templates is an important strategy in the fields of organic electronics and spintronics in order to tailor the physical properties of organic thin films to suit their intended application.